On-demand plerixafor added to high-dose cyclophosphamide and pegylated recombinant human granulocyte colony-stimulating factor in the mobilization of patients with multiple myeloma: a treatment with high effectiveness, convenient, and affordable cost - Hou, Li-qiong; Liu, Jun-Ru; Gu, Jing-Li; Chen, Mei-Lan; Kuang, Li-Fen; Huang, Bei-Hui; Zou, Wai-yi; Li, Juan (Frontiers in Oncology, 2024)
Abstract Objective: The combination of high-dose cyclophosphamide (HD-Cy) (3g/m2) plus granulocyte colony-stimulating factor (G-CSF) and on-demand plerixafor (PXF) has been considered an effective mobilization regimen of patients with multiple myeloma(MM). However, the daily multi-injection regimen of G-CSF poses challenges. This study delves into the efficiency and cost implications of a novel approach, using HD-Cy alongside pegylated G-CSF (PEG G-CSF) and on-demand PXF. Unlike G-CSF, which necessitates daily injections, the half-life of PEG G-CSF extended allows for a single injection. Methods: A retrospective analysis was conducted on 350 MM patients, which were categorized based on their mobilization regimens: Cy+PEG G-CSF+/-PXF (n=66), Cy+PEG G-CSF (n=91), Cy+ G-CSF (n=169), and G-CSF+PXF (n=24). Results: Mobilization with Cy+PEG G-CSF+/-PXF(8.79)yielded a notably higher median CD34+ cell count compared to the other regimens: Cy+PEG G-CSF(4.96), Cy+G-CSF (4.65), and G-CSF+PXF (2.99) (P<0.001). The percentage of patients who achieved >6×106/kg CD34+ cells was significantly higher in the Cy+PEG G-CSF+/-PXF group (77.3%) than in the other mobilization regimens: Cy+PEG G-CSF (41.8%), Cy+ G-CSF (37.3%), and G-CSF+PXF (8.3%) (P<0.001). From a cost perspective, the Cy+PEG G-CSF+/-PXF approach was more economical than the G-CSF+PXF strategy but was marginally costlier than the other two methods. A multivariate assessment highlighted that the combination of Cy+PEG G-CSF with on-demand PXF had a superior potential to achieve the desired harvest (6×106/kg) compared to the Cy+PEG G-CSF protocol without PXF. The incremental cost-effectiveness ratio for each 1% increase in the probability of achieving a successful optimal harvest was $ 97.02 per patient. The incidence of neutropenic fever was 3.0% in the Cy+PEG G-CSF+/-PXF group . Conclusion: The combination of on-demand PXF with HD-Cy and PEG G-CSF offers a cost-effective approach with a high mobilization success rate, manageable side effects, and the convenience of fewer injections. It stands as a promising mobilization strategy for MM patients.